A simple approach to achieve polarization diversity in broadband reflectarrays using single‐layered rectangular patch elements. Issue 2 (February 2015) - Guo, Lu; Tan, Peng‐Khiang; Chio, Tan‐Huat
ABSTRACT This article presents a simple method to realize polarization diversity in broadband reflectarrays. The wideband characteristic of the reflectarray is achieved using rectangular patch elements arranged in a subwavelength grid on a single layer of substrate; while the polarization diversity of the reflectarray is obtained by simply rotating the feed horn antenna. As the two orthogonal x‐ and y‐component of the rectangular patch element demonstrate relatively negligible interaction, the circular polarized (CP) reflectarrays with linearly polarized feed that have been proposed previously are found to be capable of supporting quadruple polarizations by means of rotating the feed. Based on the rectangular patch elements, an offset‐fed 405 × 405 mm2 reflectarray with 0.3λ grid and centered at 10 GHz is designed and developed for right‐hand circular polarization (RHCP). In an effort to realize the polarization diversity, the feed horn antenna is subsequently rotated relative to the array with angles of 0°, 90°, and 135° for vertical polarization, horizontal polarization, and left‐hand circular polarization (LHCP), respectively. The viability and effectiveness of the proposed simple method for polarization diversity is experimentally verified. The measured results show that the 1‐dB gain bandwidth for all four polarizations can reach as large as 18%. Furthermore, the 3‐dB axial ratio bandwidths for CP operations are remarkably wide, above 36% and 40% for RHCP and LHCP, respectively. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:305–310, 2015